DEVELOPMENT APPLICATIONS ANIMATION OF PLANET FOR BASIC SCHOOL STUDENTS USING Macromedia Flash 5.0 - Nur Rakhmawanti; Melani Dewi Lusita, SKom, MMSI (Jurnal Sistem Informasi, 2005)
Planet, which is the part of the solar system that orbit the sun. Scientific writing aims to create animations planet that can be used as a means of information for all general and especially among elementary school students about the planets that are in this universe. In this scientific writing will be discussed how to make a simple animation planet is also interactive and interesting. It also included some information about the planet. In writing this scholarly authors use the program Macromedia Flash 5.0 applications are already known as a maker of application program animation and also by using other software such as Swift 3D 2.0 to create the object modeling and animation swf format and Ulead COOL 3D 2.0 Trial to make the various effects of writing three gif format dimensions. Authors used the method of using literature study drawn from several books and CDs Encarta Encyclopedia Deluxe 2000.